PEMBELAJARAN PEMISAHAN CAMPURAN GARAM BERBASIS STEM DAPAT MENINGKATKAN KETERAMPILAN KOLABORATIF SISWA SMP NEGERI 36 JAKARTA - Carsono, Adi; Heliawati, Heliawati; Permana, Irvan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the improvement of collaborative skills of students of SMP Negeri 36 Jakarta through STEM-based salt mixture separation learning. Collaborative problem solving is recognized as one of the key competencies of the 21st century by the Organization for Economic Co-operation and Development. This concept of collaboration includes not only cooperation, but also communication, negotiation, sharing responsibility, and achieving joint solutions. The interest and involvement of students in collaborative learning depend not only on the group structure, but also on the quality of social interactions that occur during the learning process. Meanwhile, science learning includes four main elements, namely attitudes, processes, products, and applications. The four elements of science learning are realized through learning activities. The skills possessed in science learning are called process skills, while the attitudes that must be possessed are also called scientific attitudes. One of the new pedagogical perspectives is the STEM concept, this term and its related methods are used in connection with educational policies and curriculum choices to promote and support the development of science and technology. ABSTRAKPenelitian ini bertujuan untuk menganalisis peningkatan keterampilan kolaboratif siswa SMP Negeri 36 Jakarta melalui pembelajaran pemisahan campuran garam berbasis STEM. Pemecahan masalah kolaboratif diakui sebagai salah satu kompetensi kunci abad ke-21 oleh Organisasi untuk Kerja Sama dan Pembangunan Ekonomi. Konsep kolaborasi ini tidak hanya mencakup kerja sama, tetapi juga komunikasi, negosiasi, berbagi tanggung jawab, dan pencapaian solusi bersama. Minat dan keterlibatan peserta didik dalam pembelajaran kolaboratif tidak hanya bergantung pada struktur kelompok, tetapi juga pada kualitas interaksi sosial yang terjadi selama proses pembelajaran. Sementara itu pembelajaran IPA mencakup empat unsur utama, yaitu sikap, proses, produk, dan aplikasi. Keempat unsur pembelajaran IPA tersebut diwujudkan melalui kegiatan pembelajaran. Keterampilan yang dimiliki dalam pembelajaran IPA disebut keterampilan proses, sedangkan sikap yang harus dimiliki disebut juga sikap ilmiah. Salah satu perspektif pedagogi baru adalah konsep STEM, istilah ini dan metode terkaitnya digunakan sehubungan dengan kebijakan pendidikan dan pilihan kurikulum untuk mempromosikan dan mendukung pengembangan ilmu pengetahuan dan teknologi.